OTORITAS KYAI PENGASUH DI PONDOK PESANTREN AL-FANANI UNIVERSITAS MUHAMMADIYAH JEMBER - Nursyamsiyah, Siti (Universitas Muhammadiyah Jember, 2018)
Islamic boarding schools as an Islamic educational institution dated back from the history of Islamic ideology, especially in Indonesia, and cannot be separated from specific type of leadership called Kyai. Kyai is usually considered as a source of absolute power and authority in the life and environment of pesantren (i.e., Islamic boarding schools). So all policies both from the purpose up to implementation come from one authority. Kyai controls all sectors of Islamic boarding school. This fact normally leads to the formation of absolute authority by Kyai. Tahfidzul Qur'an Al-Fanani Islamic Boarding School, based on the results of a preliminary study, provides a different portrait in comparison with other Islamic boarding schools. Tahfidzul Qur'an Al-Fanani Islamic Boarding School, which was founded by Universitas Muhammadiyah Jember, becomes an interesting phenomenon to study. The questions of this study were formulated as follows: 1. What form of authority is applied in the Tahfidzul Qur'an Al-Fanani boarding school? 2. What factors support and inhibit leadership in Tahfidzul Qur'an Al-Fanani Islamic boarding school? 3. How does leadership authority affect the existence of ‘santri’ in the Tahfidzul Qur'an Al-Fanani boarding school? This study aimed to find a comprehensive picture of the leadership model in Al-Fanani boarding school. This study employed a qualitative approach involving interviews and documentation. Data analysis technique was triangulation. The findings show that, first, the form of authority is traditional. Second, the supporting factor is rote learning becomes the authority of each teacher (ustadz), not the leader. Meanwhile, the inhibiting factor lies in the difference between the status of ‘santri’ from ordinary students. Finally, third, Kyai affected the number of santri, which does not increase every year.